A comparison of methods to assess site index in young Norway spruce stands - Jakobsen , Niels Aagaard (2014)
This study investigates whether the site index curve method (SICM) and the growth intercept method (GIM) can be used for site index predictions in younger Norway spruce (Picea abies (L.) Karst.) stands than recommended by current guidelines. For SICM it was thus investigated whether the method could be used for stands younger than ten years, and for GIM it was tested whether a starting point for the intercept measurements could be used below the recommended 2.5 meter. This was tested based on measurements taken from experimental stands in Tönnersjöheden Research Forest. For GIM it was found that the method can only be used when the TH-trees of a stand have five complete intercepts above 2.5 meters. For the method to be applicable beyond this, it will be necessary to adapt the underlying equations, perhaps following the Canadian example where a 1.3 meter intercept start is used. In conclusion it is not currently possible to apply the approach beyond the current recommendations.